Phylogeny of Canthocamptidae (Copepoda, Harpacticoida) based on the morphology of antennae and mouthparts - A.A. Novikov; E.N. Abramova; R.M. Sabirov (Учёные записки Казанского университета: Серия Естественные науки)
The plesiomorphic state of mouthparts and antennae, both characterized by dense setation and numerous spine groups, was described in a hypothetical common ancestor of all canthocamptids. This is the first time that canthocamptids have been subjected to a comparative analysis based on not only segmentation and ornamentation of their appendages, but also on spinular ornamentation. All data were entered into a matrix with 131 characters. Phylogenetic relationships were inferred in PAUP 4.0: a total of 41 species were divided into several major clades – Cletocamptus, Hemimesochrinae, Mesochra + Heteropsyllus, Itunella + Taurocletodes, Canthocamptinae + Morariinae. In general, the results obtained coincided with the available molecular genetic data. In the Canthocamptinae + Morariinae clade, Canthocamptus and Bryocamptus were supported as the sister genera. However, some genera were deemed to be non-monophyletic and, therefore, should be separated: Cletocamptus, Mesochra, possibly Attheyella, Bryocamptus, Moraria.